The giant encyclopedia of circle time and group activities for children 3 to 6 : over 600 favorite circle time activities created by teachers for teachers - Charner, Kathy (Beltsville, Md. : Gryphon House, 1996)
Contains more than six hundred circle time and group activities designed by teachers to use with children three to six years old, each including a suggested age, a list of materials, and step-by-step directions, and features lists of related books, songs, and poems.
Includes indexes.
Elem. School Library Collection.
Professional
Keywords: Creative activities and seat work; Early childhood education -- Activity programs; Group work in education; Cooperative learning; Creative activities; Early childhood education